Teungku Dayah Agency and Religious Social Capital on Drug Eradication in Aceh, Indonesia - Nirzalin Nirzalin; Yogi Febriandi (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
This article examines the success of religious social capital and the agency of teungku dayah (Islamic scholars who belong to traditional religious school) in the collective drug eradication movement in Ujong Pacu, Lhokseumawe-Aceh, Indonesia. The role of religious social capital in combating the drugs market in global drug policy has been less studied. This study provides a quite different view from most scholars who work for combating drug dealers by engaging participation of religious communities in rural society. The agency of teungku dayah succeeded in mobilizing the villagers due to the social capital that bonded the community based on religious ties. The article used live-in method, observation, in-depth and interviews to build a sociological imagination about  the patterns of social practice of the people who  become  the subject  of the research. The researchers lived in one of the villager’s houses, participated in their discussions, listened to the gossip, worshipped with them and were involved in certain jobs carried out by the community members who targeted informants. Using religious social capital, this article argues that teungku dayah effectively  used  the social and  religious capital  of the Ujong Pacu community to conduct drug eradication. Religious social capital has strong ties in unifying elements of the people in the same religion, moreover it becomes an energy that keeps motivating the community to run anti-drugs movement and driving out the drug addicts in Ujong Pacu, Lhokseumawe-Aceh.